Penerapan Model Project Based Learning (PjBL) untuk Meningkatkan Berpikir Kreatif dan Prestasi Belajar - Buyung, Buyung (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research aims to describe the application of the Project Based Learning (PjBL) model to improve creative thinking and learning achievement. The research design used action research and continued with quasi experiments. The action cycle is carried out in 3 cycles. Quasi experiments use one experimental class and one control class. The subjects of this research were 27 class A students in the even semester of the 2023-2024 academic year. The research sample was taken using simple random sampling, then class C was selected, totaling 28 people as the experimental class, while class B was 27 people as the control class. Data collection uses observation sheets and tests. Data analysis uses observational analysis of the application of learning models, analysis of creative thinking and learning achievement using the t test. The results of this research show that the application of the project based learning (PjBL) model can improve creative thinking, increase achievement and effectively improve learning achievement in media and learning resource development courses.